2009
DOI: 10.1002/sce.20344
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, learning, and transformative experience: A study of deep engagement in science

Abstract: This study investigated the prevalence of transformative experiences, antecedents of transformative experience, and the relation between transformative experience and deep-level learning (conceptual change and transfer) for high school biology students (N = 166). Results suggested that the high school students in our sample typically engaged in low levels of transformative experience with respect to biology, but those students who strongly identified with science and who endorsed a mastery goal orientation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
162
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(178 citation statements)
references
References 73 publications
(79 reference statements)
10
162
0
6
Order By: Relevance
“…According to Roeser (2004), the correlation between performance-approach and performance-avoidance goals went up to as high as .90 among samples of U.S. students, after correcting for unreliability in the assessment scales. Strong correlations between the two performance goals commensurate to those observed in Korean studies have been reported in other U.S. studies as well (e.g., Pugh, Linnenbrink-Garcia, Koskey, Stewart, & Manzey, 2010). A common feature in the studies reporting particularly strong correlations between approach and avoidance components is the definition of performance goals that emphasizes both normative competence and validation of ability.…”
Section: Achievement Goal Dichotomy: Back To Where It Startedsupporting
confidence: 79%
“…According to Roeser (2004), the correlation between performance-approach and performance-avoidance goals went up to as high as .90 among samples of U.S. students, after correcting for unreliability in the assessment scales. Strong correlations between the two performance goals commensurate to those observed in Korean studies have been reported in other U.S. studies as well (e.g., Pugh, Linnenbrink-Garcia, Koskey, Stewart, & Manzey, 2010). A common feature in the studies reporting particularly strong correlations between approach and avoidance components is the definition of performance goals that emphasizes both normative competence and validation of ability.…”
Section: Achievement Goal Dichotomy: Back To Where It Startedsupporting
confidence: 79%
“…Here, the teaching of science is actively seeking a merger with the arts to produce an emotionally charged experience by which the educative goals are attained [20]. Techniques related to the artistic crafting of science education are recommended as practical methodology and have been put to test with students for empirical evaluation of this learning model [16,21].…”
Section: Presenting the Natural Worldmentioning
confidence: 99%
“…'Engagement' relates to the intensity and emotional quality of a students' involvement in learning and has been variously described as having affective (e.g., interest), behavioural (e.g., persistence) and cognitive dimensions (e.g., deep level learning strategies) (Fredricks, Blumenfeld & Paris, 2004;Pugh, Linnenbrink-Garcia, Koskey, Stewart, & Manzey 2009). The affective dimension of students' engagement with science learning was a recurring theme in the teachers' commentary.…”
Section: Facilitating Participation In Vce Level Sciencementioning
confidence: 99%